Management of Cancer and Health After the Clinic Visit: A Call to Action for Self-Management in Cancer Care. (11th June 2020) - Howell, Doris; Mayer, Deborah K; Fielding, Richard; Eicher, Manuela; Verdonck-de Leeuw, Irma M; Johansen, Christoffer; Soto-Perez-de-Celis, Enrique; Foster, Claire; Chan, Raymond; Alfano, Catherine M; Hudson, Shawna V; Jefford, Michael; et al.
Abstract: Individuals with cancer and their families assume responsibility for management of cancer as an acute and chronic disease. Yet, cancer lags other chronic diseases in its provision of proactive self-management support in routine, everyday care leaving this population vulnerable to worse health status, long-term disability, and poorer survival. Enabling cancer patients to manage the medical and emotional consequences and lifestyle and work changes due to cancer and treatment is essential to optimizing health and recovery across the continuum of cancer. In this paper, the Global Partners on Self-Management in Cancer puts forth six priority areas for action: Action 1: Prepare patients and survivors for active involvement in care; Action 2: Shift the care culture to support patients as partners in cocreating health and embed self-management support in everyday health-care provider practices and in care pathways; Action 3: Prepare the workforce in the knowledge and skills necessary to enable patients in effective self-management and reach consensus on core curricula; Action 4: Establish and reach consensus on a patient-reported outcome system for measuring the effects of self-management support and performance accountability; Action 5: Advance the evidence and stimulate research on self-management and self-management support in cancer populations; Action 6: Expand reach and access to self-management support programs across care sectors and tailored to diversity of need and stimulation of research to advance knowledge. It is time for a revolution to better integrate self-management support as part of high-quality, person-centered support and precision medicine in cancer care to optimize health outcomes, accelerate recovery, and possibly improve survival.